Radiation pneumonitis in relation to pulmonary function, dosimetric factors, TGFβ1 expression, and quality of life in breast cancer patients receiving post-operative radiotherapy: a prospective 6-month follow-up study. - ÇİMŞİT, CANAN (My University, 2022)
Purpose To investigate development of radiation pneumonitis (RP) in relation to pulmonary function, dosimetric factors, and transforming growth factor beta-1 (TGFβ1) expression in irradiated breast cancer patients. Methods A total of 49 breast cancer patients who received post-operative radiotherapy (RT) were evaluated in terms of pulmonary function tests (PFTs), quality of life (QoL), development of RP, dosimetric factors, cytokine levels, and lung highresolution computed tomography (HRCT) before and after RT. ROC analysis was performed for performance of dosimetric factors in predicting RP, while frequencies of single nucleotide polymorphisms (SNPs) genotyped for TGFβ1 (rs11466345 and rs1800470) were also evaluated. Results All cases with RP (10.2%) recovered clinically at the end of third post-RT month. PFT and HRCT parameters were similar before and after RT overall, as well as by RP and the radiation feld subgroups. ROC analysis revealed the signifcant role of the ipsilateral V5 (cutof value of 45.9%, p=0.039), V10 (29.4%, p=0.015), V20 (23%, p=0.017), and MLD (1200 cGy, p=0.030) in predicting RP. Higher post-RT TGFβ1 levels (p=0.037) were noted overall and in patients with RP. Patient and control groups were similar in terms of frequencies of SNPs genotyped for TGFβ1 (rs11466345 and rs1800470). EORTC QLQ-C30 and QLQ-BR-23 scores were similar in patients with vs. without RP. Conclusion Our fndings revealed signifcant role of dosimetric factors including MLD, V20 as well as the low dose-volume metrics in predicting the risk of RP among breast cancer patients who received post-operative RT. Implementation of RT, extent of radiation feld or the presence of RP had no signifcant impact on PFTs
Keywords: Breast cancer; Radiotherapy; Radiation pneumonitis; Pulmonary function; Dosimetric factors; TGFß1